PELAKSANAAN TUGAS JURUSITA PADA PERKARA PERDATA - Rahman , Erik; Khalid, Hasbuddin; Arief, Anggreany (Qawanin Jurnal Ilmu Hukum, 2022)
ABSTRACT This study aims to determine the implementation of the bailiff's duties in civil cases based on Article 103 of the Republic of Indonesia Law Number 7 of 2021 and to find out the supporting and inhibiting factors in the process of implementing the bailiff's duties at the Watansoppeng Religious Court. This study uses empirical legal research methods, namely legal research that focuses on research on the legal reality in society. The results of this study show that the judicial process based on article 103 of the Republic of Indonesia Law Number 7 of 1989 concerning Religious Courts at the Watansoppeng Religious Court Office has so far been in favor of the general public in providing justice services and focusing on improving and accelerating the settlement of cases handled by personnel. judiciary. And the supporting factors for the implementation of the bailiff's duties/surrogate bailiffs for the Watansoppeng Religious Court are the provision of performance benefits, and security guarantees in the implementation of tasks in the field. While the inhibiting factors for bailiffs are the lack of public understanding of the summoning procedure, lack of coordination with other agencies, the lack of porcelain from the village, lack of supporting facilities, environmental and natural conditions and the provision of fake numbers. The research recommendation is that further research is still needed on bailiffs, which is not only limited to the implementation of Article 103 of the Republic of Indonesia Law Number 7 of 1989 concerning the Religious Courts, but also on other articles and laws related to confiscation. ABSTRAK Penelitian ini bertujuan untuk untuk mengetahui Pelaksanaan Tugas Jurusita Perkara Perdata berdasarkan Pasal 103 Undang-Undang RI Nomor 7 Tahun 2021 Serta untuk mengetahui faktor Pendukung dan Penghambat dalam proses Pelaksanaan Tugas Jurusita pada Pengadilan Agama Watansoppeng. Penelitian ini menggunakan metode penelitian hukum empiris, yaitu penelitian hukum yang memfokuskan penelitan pada realitas hukum dalam masyarakat. Hasil Penelitian ini menunjukkan Proses Pelaksanaan kejurusitaan berdasarkan pasal 103 Undang-Undang RI Nomor 7 Tahun 1989 Tentang Peradilan Agama pada Kantor Pengadilan Agama Watansoppeng selama ini, berpihak kepada masyarakat umum dalam memberikan pelayanan keadilan dan fokus pada peningkatan maupun percepatan penyelesaian perkara yang di tangani oleh tenaga kejurusitaan. Dan Faktor Pendukung Pelaksanaan Tugas Jurusita/Jurusita Pengganti Pengadilan Agama Watansoppeng yaitu pemberian tunjanan kinerja, dan diberi jaminan keamanan dalam pelaksanaan tugas-tugas dilapangan. Sedangkan Faktor Penghambat Jurusita yaitu, Minimnya pemahaman masyarakat tentang prosedur pemanggilan, Kurangnya koordinasi dengan instansi lain, Kurangnya jumlah porsenil dari kelurahan, kurangnya sarana penunjang, Keadaan lingkungan dan alam Lingkungan dan pemberian nomor palsu. Rekomendasi penelitian yaitu masih perlu penelitian lebih lanjut tentang jurusita yang tidak hanya terbatas pada implementasi pasal 103 Undang-Undang RI Nomor 7 Tahun 1989 Tentang Peradilan Agama, tetapi juga terhadap pasal-pasal lain dan Undang-Undang yang terkait dengan kejurusitaan.